Automatic Control Systems for Fish Box Cooler - Eviyanti, Gusrini Nelda; Prayetno, Eko (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2019)
One factor is the low yields of fish fisheries production storage techniques are not maximal. In the system of fishing in Riau Islands,generally using small weights of motor boats, fishing gear and storage techniques are simple (conventional). Due to modern cooling system is quite expensive, fishermen only use containers containing ice cubes as a coolant to keep them fresh in a few hours. The objective of the study is, designing an automatic control system forfish box cooler with a constant temperature in the fish box. The device consistsof the research isa heatsink, Peltier, temperature gauge, and pump. The device is a system in this study using a temperature sensor and Bluetooth. The results of sensor readings will be processed using the Arduino Uno is integrated with Bluetooth and then sent to the android application. The data are in the Android application will be monitored based on the desired temperature (setpoint).